Utilization of Bottom Ash Coal and Agarwood in Waste Water Treatment in Palembang Jumputan Fabric - Eis Sri Hartati; Muhammad Hatta Dahlan; Tuti Indah Sari (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
Liquid waste is easily recognized because of the presence of dyes. Waste containing dyes can cause visual pollution and increase the risk of environmental and health damage. The aim of this study was to determine the operating conditions of the best jumputan liquid waste treatment using bottom ash batubara and agarwood with variations in feed flow rate (1, 2, and 3 l/minutes), filtration time (30, 60, 90, and 120 minutes), and treatment. The results of jumputan liquid waste treatment are compared with the parameters of Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), and pH of clean water quality standards for jumputan industry businesses and/or activities regulated in the Governor’s of Sumatera Selatan Regulation Number 16 of 2005 concerning Wastewater Quality Standards. The initials analysis of jumputan liquid waste before processing showed that jumputan liquid waste did not meet these quality standards, except pH and turbidity levels. In this study, jumputan liquid waste was pre-treated using coal bottom ash and activated carbon, then filtered. Biodegradation of jumputan liquid waste by konvensional method. The best of BOD, COD, TSS, pH, and the percentage of color rejection in the study were obtained in the treatment of jumputan liquid waste using bottom ash batubara and activated carbon at a 120 minutes filtration time and a 1 l/minutes feed flow rate namely BOD 5.98 mg/l, COD 15 mg/l, TSS 22.3 mg/l, pH 7.32, color 5 Pt-Co, and 0 NTU turbidity. The filtration with bottom ash coal and agarwood can removed the coloring from dyes.